2018
DOI: 10.3389/fnmol.2018.00336
|View full text |Cite
|
Sign up to set email alerts
|

Drug Screening Identifies Sigma-1-Receptor as a Target for the Therapy of VWM Leukodystrophy

Abstract: Vanishing white matter (VWM) disease is an autosomal genetic leukodystrophy caused by mutations in subunits of eukaryotic translation initiation factor 2B (eIF2B). The clinical symptoms exhibit progressive loss of white matter in both hemispheres of the brain, accompanied by motor functions deterioration, neurological deficits, and early death. To date there is no treatment for VWM disease. The aim of this work was to expedite rational development of a therapeutic opportunity. Our approach was to design a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 53 publications
(74 reference statements)
1
36
0
Order By: Relevance
“…In mouse cultures, only 13 DEGs between VWM and control were found, of which some genes have been related to VWM disease mechanisms previously. 28 Interestingly, VWM mouse cultures also showed increased Ets1 expression. Previous studies showed an increase in CD44 expression in VWM patient white matter astrocytes in postmortem tissue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In mouse cultures, only 13 DEGs between VWM and control were found, of which some genes have been related to VWM disease mechanisms previously. 28 Interestingly, VWM mouse cultures also showed increased Ets1 expression. Previous studies showed an increase in CD44 expression in VWM patient white matter astrocytes in postmortem tissue.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed an impaired SHH pathway in primary astrocytes from the Eif2b5 R132H/R132H mouse, confirming the involvement of the SHH pathway in VWM. 28 Interestingly, VWM mouse cultures also showed increased Ets1 expression. Ets1 is a transcription factor that is involved in the T-cell immune response and was shown to be upregulated in astrocytes surrounding white matter lesions in a mouse model for multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While not significant, SHH and SMO levels were also decreased (2-2.5 fold) in VWM white matter-like astrocytes. A recent study showed an impaired SHH pathway in primary astrocytes from the Eif2b5 R132H/R132H mouse, confirming the involvement of the SHH pathway in VWM (Atzmon et al, 2018). Interestingly, VWM mouse cultures also showed increased Ets1 expression.…”
Section: Discussionmentioning
confidence: 74%